STRATEGI SAMUDRA PUTIH: MEMANFAATKAN ISU SAMPAH PLASTIK UNTUK MENCIPTAKAN PELUANG BISNIS PRODUK WAKAKA™ - Sulaiman Girivirya (Komitmen: Jurnal Ilmiah Manajemen, 2023)
The only group representing the Sriwijaya State Buddhist College (STABN) to enter the Student Creativity Development Competition in the Entrepreneurship (PKM-K) competition is the 2022 WAKAKA™ product. Conceptualization and business implementation are raised from the issue of plastic waste. Of course, this issue is a serious problem in many developing countries, including Indonesia. Science and technology have invented ingenious tools to recycle plastic waste into economically valuable recycling materials. PKM-K WAKAKA™ works with producer partners to purchase finished products in the form of T-shirts and hoodies. This product also inspires consumers through the simplicity and wisdom of Zen in the artwork and calligraphy that is printed on the product. Products named with the WAKAKA™ trademark: Wahana Karya Wisdom develop businesses using the White Ocean Strategy. Steps are taken to proclaim or promote to save the planet by reducing plastic waste (reduce), reusing used goods (reuse) and using items made from recycled materials (recycle), Inspiring the community and the students themselves through Zen wisdom. In social steps, Buddhist entrepreneurship is practiced theoretically. Based on the literature review, the white samudara strategy business concept is suitable for product development in the PKM-K program held by the Directorate General of Buddhist Community Guidance, Ministry of Religion of the Republic of Indonesia.